2013
DOI: 10.1111/sms.12069
|View full text |Cite
|
Sign up to set email alerts
|

The effects of physical activity and exercise on brain‐derived neurotrophic factor in healthy humans: A review

Abstract: The purpose of this study was to summarize the effects of physical activity and exercise on peripheral brain-derived neurotrophic factor (BDNF) in healthy humans. Experimental and observational studies were identified from PubMed, Web of Knowledge, Scopus, and SPORT Discus. A total of 32 articles met the inclusion criteria. Evidence from experimental studies suggested that peripheral BDNF concentrations were elevated by acute and chronic aerobic exercise. The majority of the studies suggested that strength tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
271
3
14

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(302 citation statements)
references
References 60 publications
14
271
3
14
Order By: Relevance
“…However, Schiffer et al 29 describe no influence of aerobic training on resting BDNF levels in healthy sport students and most studies did not observe an influence of strength training on BDNF concentrations. 6 We speculate that acute and chronic changes of BDNF concentrations depend on age, the type of exercise, and the individual level of physical fitness before training.…”
Section: Structural Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…However, Schiffer et al 29 describe no influence of aerobic training on resting BDNF levels in healthy sport students and most studies did not observe an influence of strength training on BDNF concentrations. 6 We speculate that acute and chronic changes of BDNF concentrations depend on age, the type of exercise, and the individual level of physical fitness before training.…”
Section: Structural Resultsmentioning
confidence: 90%
“…Most studies suggest that both acute and enduring aerobic exercise lead to BDNF concentration elevations. 6 Brain-derived neurotrophic factor, a neurotrophin, is widely expressed in the brain, and influences neuronal survival, differentiation, axonal path-finding, regulation of dendritic trafficking to postsynaptic densities, 7 protection against neuronal death in the hippocampus, 8 and induction and maintenance of late-phase long-term potentiation. 9 Thus, BDNF is critically important to the cellular and subcellular processes that underlie learning and memory in healthy subjects and agingrelated diseases.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, various subtypes of leukocytes can secrete S100B (Miki et al, 2013;Fujiya et al, 2014;Moutsatsou et al, 2014). Thrombocytes are the largest source for serum BDNF (Fujimura et al, 2002), adipocytes produce both S100B and BDNF (Fujiya et al, 2014;Huang et al, 2014), finally NSE may originate from damaged peripheral nerves (Li et al, 2013). Because we did not assume relevant biases related to these potentially confounding sources in minor depression, we did not control for potential non-brain sources of the serum markers in our study.…”
Section: Limitationsmentioning
confidence: 99%
“…Another review by Zoladz et al [114] found consistent results regarding acute exercise but found the relationship between resting BDNF increases and chronic exercise less consistent. Further, a review done by Huang et al [115] found increases in peripheral BDNF concentrations in relation to both acute and chronic aerobic exercise. In short and of great importance to the EPIC treatment, there is a consistent increase in BDNF both promoting neuro-and synaptogenesis and cognitive enhancement after a single acute bout of aerobic exercise whereas the effects of chronic aerobic exercise training on BDNF levels is less clear.…”
Section: Nvc Re-regulationmentioning
confidence: 99%